Of Heroes and Magic: The Epics of Mindanao - Godinez-Ortega, Christine (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper is an introduction to the study of Mindanao's ethno-epics that were discovered, recorded and studied by the country's scholars in the last 20 years. It mentions the epic herq,es Bantogen, Tudbulol and 1imuay Pamulew who possessed amulets, magical weapons and animals as part of the eventful lives they led in their fabled kingdoms. There is a brief discussion of the epics' commonalities in the motifs, imagery, value systems, etc. and emphasizes that the events in the epics happened before the spread oi Islam and Christianity in Mindanao. The paper raises the need for an approach to study these epics and suggests their promotion especially among school children to instill in them the love of their own cultural heritage at an early stage. Finally, the paper urges the study of these epics as an aid to fill in gaps of our pre-colonial past to promote peace among Mindanao's tri peoples: the Muslims, Lumads and the third and fourth generations of Christian settlers.